Gender differences in supervisors' multidimensional performance ratings: Large sample evidence. Issue 5 (19th October 2016) - Stone, Thomas H.; Foster, Jeff; Webster, Brian D.; Harrison, Jennifer; Jawahar, I. M.
ABSTRACT: We examined gender differences in supervisor ratings of overall job performance and 37 performance dimensions. Based on data from a large, diverse sample of managers ( N = 3, 367) and nonmanagers ( N = 9, 670), we found that gender had only minimal effects on ratings for a small number of specific job performance dimensions. This was generally true regardless of whether the job performance dimension was more agentic or communal in nature, whether the job was a managerial or a nonmanagerial position, and regardless of the proportion of men or women that traditionally occupy a specific job. Overall, our results are more consistent with the gender similarities hypothesis than the agency/communion paradigm, role congruity theory, and the lack of fit model. We discuss future research avenues and implications.